Genetic variant rs3750625 in the 3′UTR of ADRA2A affects stress-dependent acute pain severity after trauma and alters a microRNA-34a regulatory site. Issue 2 (February 2017) - Linnstaedt, Sarah D.; Walker, Margaret G.; Riker, Kyle D.; Nyland, Jennifer E.; Hu, JunMei; Rossi, Catherine; Swor, Robert A.; Jones, Jeffrey S.; Diatchenko, Luda; Bortsov, Andrey V.; Peak, David A.; McLean, Samuel A.
Abstract : Abstract: α2A adrenergic receptor (α2A-AR) activation has been shown in animal models to play an important role in regulating the balance of acute pain inhibition vs facilitation after both physical and psychological stress. To our knowledge, the influence of genetic variants in the gene encoding α2A-AR, ADRA2A, on acute pain outcomes in humans experiencing traumatic stress has not been assessed. In this study, we tested whether a genetic variant in the 3′UTR of ADRA2A, rs3750625, is associated with acute musculoskeletal pain (MSP) severity following motor vehicle collision (MVC, n = 948) and sexual assault (n = 84), and whether this influence was affected by stress severity. We evaluated rs3750625 because it is located in the seed binding region of miR-34a, a microRNA (miRNA) known to regulate pain and stress responses. In both cohorts, the minor allele at rs3750625 was associated with increased musculoskeletal pain in distressed individuals (stress*rs3750625 P = 0.043 for MVC cohort and P = 0.007 for sexual assault cohort). We further found that (1) miR-34a binds the 3′UTR of ADRA2A, (2) the amount of repression is greater when the minor (risk) allele is present, (3) miR-34a in the IMR-32 adrenergic neuroblastoma cell line affects ADRA2A expression, (4) miR-34a and ADRA2A are expressed in tissues known to play a role in pain and stress, (5) following forced swim stress exposure, rat peripheral nerve tissue expression changes are consistent with miR-34a regulation of ADRA2A . Together, these results suggest that ADRA2A rs3750625 contributes to poststress musculoskeletal pain severity by modulating miR-34a regulation. Abstract : Supplemental Digital Content is Available in the Text. ADRA2A variant rs3750625 alters an miR-34a binding site and is associated with acute pain severity following motor vehicle collision and sexual assault traumas.